Deciphering the role of β-phase Bi2O3 nanorods incorporated on g-C3N4 nanosheets for efficient pollutant removal. (May 2022) - Nagar, Aashna; Basu, Soumen
Abstract: Photocatalysis, a facile and inexpensive technique for degrading toxins requisites compounds with high efficacy. Currently, β-Bi2 O3 /g-C3 N4 nanosheets were fabricated through the in-situ precipitation process. The photocatalysts were studied via XPS, HR-TEM-EDX, FESEM-EDS, XRD, UV-DRS, elemental mapping, and PL analysis. A flaky nanosheets-like structure having a small bandgap (2.02 eV) and less recombination capacity was procured. A mesoporous structure (25.59 nm) with an immense surface area (63 m 2 /g) was acquired via the BET N2 adsorption-desorption technique. The 1:3 β-Bi2 O3 /g-C3 N4 composite photodegraded fipronil (FIP) and methylene blue (MB) with ∼75% and ∼97% efficacy with rate constants, 0.01068 min −1 for FIP and 0.04066 min −1 for MB. The results were accredited to the heterojunction between Bi2 O3 nanorods and g-C3 N4 nanosheets. pH, catalyst concentration studies displayed the maximum efficiency of 97.54% for MB at pH 8 and 74.28% for FIP at pH 4 via a catalyst dose of 0.06 g/L. The scavengers unveiled the involvement of hydroxide radical ( ● OH) in the degradation process. The durability of the composite was tested for four repetitive cycles with 88.99%, 71.84% efficacy for MB and FIP, respectively with XRD analysis scrutinizing the structural intactness of the composite. The nanoflake-like composite caters to a competent photocatalyst useful for toxicant removal. Graphical abstract: Image 1 Highlights: Z-scheme β-Bi2 O3 /g-C3 N4 composite designed via the in-situ method. β-Bi2 O3 nanorods deposited on g-C3 N4 nanolayers. ∼97% and ∼75% degradation efficacy in visible light for MB and FIP respectively. Hydroxyl radicals responsible for the photodegradation process.